ILMU HUKUM DAN PERKEMBANGANYA (KAJIAN KHUSUS HUKUM NORMATIF) - Imam Mahdi (Universitas Islam Negeri Fatmawati Sukarno, 2016)
The main aim in this paper is to determine the specificity of the nature of the science of law (being suigeneris) and the development of the jurisprudence of the various schools that dominate the priodesasi the development of science in general. Besides, it is also about schools posistisme studied law which is still to be the center of various legal studies, although these schools has been criticized by experts, especially after the emergence of the theory of relativity sebagaiman effect on natural sciences (exact). Indonesia actually embrace pluralism in the law, but in practice dominated by the understanding of legal positivism. This understanding on the one hand a major contribution to the establishment of law in Indonesia, especially in relation to the legal hierarchy. In another section of this paper provides a practical overview of normative law as a form of research with various ragaan easily understood. It mainly deals with issues or legal problems that should be put forward by the applicant in determining the design of the studies law